2013
DOI: 10.1002/hep.26220
|View full text |Cite
|
Sign up to set email alerts
|

3 Tesla diffusion-weighted MRI for assessing liver fibrosis in nonalcoholic fatty liver disease

Abstract: difficult. Nonetheless, previous work found no increased prevalence of cryoglobulinemia in patients with B cell frequencies of >20% of the lymphocyte population. 7 The decreased B cell numbers in our study do not contradict the large expansions in specific B cell clones observed in cryoglobulinemia. Clonal B cell populations in the activated/memory B cell subset drive MC, and we did not identify reductions in this subset. Rather, we found the percentage of these cells in the total B cell population to be incre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…4D), which was contrary to the expected negative correlation between the H-PDFF and the native T1 values, but Ahn JH et al[36] also proved that the liver fat content was positively correlated with native T1 values when the liver fat content was less than 30%. Although there was no signi cant difference in hepatic ADC value and NFS between the two groups, the indicators of the study group still showed more obvious liver injury than the control group, indicating that the liver diffusion function of the study group was weakened, which may be related to the decrease in liver cell diffusion function caused by hepatic steatosis and liver brosis, which was also proven by Papalavrentios L et al [37].…”
Section: Discussionmentioning
confidence: 56%
“…4D), which was contrary to the expected negative correlation between the H-PDFF and the native T1 values, but Ahn JH et al[36] also proved that the liver fat content was positively correlated with native T1 values when the liver fat content was less than 30%. Although there was no signi cant difference in hepatic ADC value and NFS between the two groups, the indicators of the study group still showed more obvious liver injury than the control group, indicating that the liver diffusion function of the study group was weakened, which may be related to the decrease in liver cell diffusion function caused by hepatic steatosis and liver brosis, which was also proven by Papalavrentios L et al [37].…”
Section: Discussionmentioning
confidence: 56%